Jeff Wall - Wall, Jeff 1946- (Gagosian, 2019)
"From his pioneering use in the 1970s of backlit color transparencies--a medium then synonymous with advertising--to his intricately constructed scenes of enigmatic incidents from daily life, literature, and film, Wall has expanded the definition of the photograph, both as object and illusion.The triptych I giardini/The Gardens (2017) was photographed in the gardens of the Villa Silvio Pellico in Moncalieri, outside of Turin, Italy. Though Wall has made several works that combine two or more images, this is the first in which the order, read from left to right, represents a passage of time. It therefore has a narrative aspect absent from any previous picture group. The three images--individually titled Appunto/Complaint, Disappunto/Denial, and Diffida/Expulsion order--trace the relations between either two or four characters through three depicted moments. A doubling effect occurs again in Pair of interiors (2018), a diptych showing either one or two couples in a lamplit living room, and in Summer Afternoons (2013), which shows what appears to be another equally introverted, younger couple in a sunny apartment. Each person appears in his or her own picture, creating uncertainty about whether the diptych depicts one or more 'summer afternoons.'"--Gagosian.com